Acrylic foam tape and preparation process thereof

By introducing nanomaterials such as cellulose nanocrystals into the tape and using dynamic polymerization and pulsed light source technology, the problem of insufficient mechanical strength and hygiene performance of the tape is solved, and the effects of high intensity, antibacterial and self-cleaning are achieved, and the application scenarios are expanded.

CN120230492APending Publication Date: 2025-07-01YANCHENG QUANGTE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510526749.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The existing tapes are insufficient in terms of mechanical strength and toughness, are prone to rupture under high impact conditions, and have poor hygiene performance, making it difficult to meet the application needs of high hygiene requirements.

Method used

The acrylic foam tape formula is adopted, which contains nanomaterials such as cellulose nanocrystals, titanium dioxide nanoparticles, chitosan nanofibers and hydroxyapatite. Through dynamic polymerization and pulsed light source induction technology, the materials are uniformly dispersed and cross-linked, and the mechanical strength and antibacterial properties are improved.

Benefits of technology

The mechanical strength and toughness of the tape are significantly improved, and have photocatalytic self-cleaning and antibacterial functions, which improves hygiene performance and stability and broadens the scope of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120230492A_ABST
    Figure CN120230492A_ABST
Patent Text Reader

Abstract

The invention provides an acrylic foam tape and a preparation process thereof, and relates to the technical field of adhesives, the acrylic foam tape comprises the following components by weight: 50-70 parts of an acrylate monomer, 0.1-1 part of a cross-linking agent, 0.1-0.5 part of an initiator, 10-30 parts of tackifying resin, 5-15 parts of a polyurethane foaming agent, and 1-5 parts of cellulose nanocrystals. 0.5 to 3 parts of titanium dioxide nano particles, 1 to 3 parts of chitosan nano fibers and 1 to 3 parts of hydroxyapatite. According to the environment-friendly adhesive tape, the cellulose nanocrystals are added, so that the mechanical strength and toughness of the adhesive tape are improved, and meanwhile, the environment-friendly characteristic is kept; the titanium dioxide nanoparticles are added to endow the adhesive tape with photocatalytic self-cleaning and antibacterial functions, so that surface dirt can be effectively decomposed and bacterium breeding can be inhibited, and the sanitation performance of a use scene is improved; the chitosan nanofibers further enhance the antibacterial performance of the adhesive tape, endow the adhesive tape with certain biocompatibility and moisture absorption performance, and improve the adaptability and stability in the use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and particularly to an acrylic foam tape and its preparation process. Background Art

[0002] The technical field of adhesives is the science and technology that studies and develops chemical materials and processes for connecting or bonding the surfaces of different materials. This field covers a wide range of application scenarios, from ordinary glues in daily life to high-performance structural adhesives used in industrial production. Adhesives usually include natural materials (such as starch, collagen) and synthetic materials (such as acrylic acid, epoxy resin, polyurethane, etc.), and provide adhesion through physical or chemical means.

[0003] However, in the prior art, most tapes are insufficient in mechanical strength and toughness, and are prone to cracking or failure under high-impact conditions. The reason is that the material formula lacks a reinforcement mechanism and cannot disperse and absorb external impact forces. In addition, the tapes in the prior art have shortcomings in terms of hygiene performance. Most of them use inert materials, and their surfaces are prone to accumulating pollutants or breeding bacteria, making it difficult to meet the application requirements with higher hygiene requirements. Therefore, improvements are needed. Summary of the Invention

[0004] The purpose of the present invention is to solve the deficiencies existing in the prior art, and to provide an acrylic foam tape and its preparation process.

[0005] To achieve the above purpose, the present invention adopts the following technical scheme: An acrylic foam tape, the acrylic foam tape includes the following components by weight: 50 - 70 parts of acrylate monomer, 0.1 - 1 part of crosslinking agent, 0.1 - 0.5 part of initiator, 10 - 30 parts of tackifying resin, 5 - 15 parts of polyurethane foaming agent, 1 - 5 parts of cellulose nanocrystals, 0.5 - 3 parts of titanium dioxide nanoparticles, 1 - 3 parts of chitosan nanofibers, 1 - 3 parts of hydroxyapatite.

[0006] Preferably, the crosslinking agent is divinylbenzene, trimethylolpropane triacrylate or ethylene glycol diacrylate, and the initiator is benzoyl peroxide, di-tert-butyl peroxide or azobisisobutyronitrile.

[0007] The present invention provides a preparation process for an acrylic foam tape, including the following steps: S1, monomer mixing and preliminary stirring, maintaining the rotation speed in the range of 230 - 500 r / min in a stirring kettle, first putting the acrylate monomer, and adding the crosslinking agent, initiator and tackifying resin under stirring, controlling the temperature in the kettle to be maintained in the range of 50 - 60 °C to obtain a preliminary mixture; S2, Dynamic Aggregation: Control the stirring intensity and monomer feeding sequence of the preliminary mixture. Alternately switch the stirring speed within the range of 200 - 400 r / min by variable-frequency stirring. Maintain the reaction temperature within the range of 55 - 65 °C. When the viscosity reaches the threshold, obtain the dynamic polymer material. S3, Nanomaterial Dispersion and Mixing: Transfer the dynamic polymer material to a shear mixer, add cellulose nanocrystals, titanium dioxide nanoparticles, chitosan nanofibers, and hydroxyapatite, and control the temperature within the range of 35 - 45 °C to obtain a nanodispersion. S4, Pulse Light Source-Induced Polymerization: Introduce a photosensitive initiator into the nanodispersion and perform intermittent irradiation using a pulsed ultraviolet light source. Stir at a stirring speed within the range of 100 - 200 r / min during the pulse interval. After irradiating for 10 - 30 min, obtain the ultraviolet-excited material.

[0008] Preferably, it further includes: S5, Progressive Crosslinking: Perform segmented compatibility of the crosslinking agent and the initiator on the ultraviolet-excited material. Inject the remaining crosslinking agent in multiple portions and add the initiator step by step. Control the temperature within the range of 45 - 55 °C and maintain the fluidity of the material at a stirring speed within the range of 100 - 200 r / min for 30 - 60 minutes to obtain the gradient crosslinked material. S6, Pulse Light Source-Induced Uniform Dispersion of Nanoparticles: Apply pulsed ultraviolet excitation inside the gradient crosslinked material. Set the light source frequency within the range of 20 - 40 Hz. Use medium-speed stirring during the pulse interval, with the rotation speed controlled within the range of 150 - 250 r / min. After irradiating for 10 - 15 minutes, obtain the nanouniform dispersion material. S7, Foam Formation and Curing: Add a polyurethane foaming agent to the nanouniform dispersion material, control the mixing temperature within the range of 65 - 75 °C, adjust the stirring speed to within the range of 150 - 300 r / min, maintain the reaction time for 30 - 40 minutes, judge the foaming process by monitoring the cell uniformity. After the foaming stage ends, cool to room temperature and let it stand for 12 - 24 hours to obtain the acrylic foam tape.

[0009] Preferably, in step S1, the stirring time of the stirring kettle is 10 - 20 minutes.

[0010] Preferably, in step S3, the shear mixer stirs at a rotation speed within the range of 3000 - 4000 r / min for 15 - 30 minutes to obtain the nanodispersion.

[0011] Preferably, in the intermittent irradiation of step S4, the light source frequency is controlled within the range of 5 - 15 Hz.

[0012] 1. Compared with the prior art, in the present invention, by adding cellulose nanocrystals, the mechanical strength and toughness of the tape are improved while maintaining its environmental protection characteristics; the addition of titanium dioxide nanoparticles endows the tape with photocatalytic self-cleaning and antibacterial functions, which can effectively decompose surface dirt and inhibit the growth of bacteria, thus improving the hygienic performance of the usage scenario; chitosan nanofibers further enhance the antibacterial performance of the tape and endow it with certain biocompatibility and moisture absorption performance, improving the adaptability and stability during use; hydroxyapatite enhances the wear resistance and surface hardness of the tape while providing biocompatibility and antibacterial auxiliary functions; in addition, the use of polyurethane foaming agent improves the uniformity and elasticity of the foam structure, thus enhancing the performance of the tape in energy absorption and impact resistance. These improvements have comprehensively enhanced the tape in terms of mechanical properties, antibacterial properties, environmental protection properties and functionality, making it more suitable for applications in scenarios with high requirements for shock absorption, self-cleaning and antibacterial properties, and broadening the application scope and value of the product.

[0013] 2. Compared with the prior art, in the present invention, in the preliminary mixing stage, by dual control of the mixing rate and temperature of acrylate monomers, crosslinking agents, initiators and tackifying resins, the full dispersion and uniform reaction of raw materials are ensured, reducing performance fluctuations that may be caused by local concentration differences. During the dynamic polymerization process, by dynamically switching the stirring intensity and the monomer feeding sequence, the control of the reaction process is achieved, solving the problem of polymerization rate imbalance that may be caused by a single stirring mode, and improving the reaction efficiency and product quality. A variety of functional nanomaterials are highly dispersed under shear force and temperature control conditions, making the structural properties of the tape reach a balance in terms of impact resistance, durability and flexibility, while enhancing the mechanical stability and bonding ability of the material. The intermittent irradiation of the ultraviolet light source is carried out in coordination with stirring, avoiding performance unevenness caused by local overheating or out-of-control photochemical reaction rate, and enhancing the photochemical stability and aging resistance of the product. It effectively broadens the application scope of adhesives in high-performance fields and simultaneously realizes the optimization of performance.

[0014] The technical solution of the present invention will be further described in detail below with reference to the drawings and embodiments. Description of the Drawings

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0016] Figure 1 It is a process flow diagram for the preparation of an acrylic foam tape proposed by the present invention. Detailed Embodiments

[0017] Next, in combination with the accompanying drawings in the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.

[0018] Example 1, the present invention provides an acrylic foam tape. The acrylic foam tape comprises the following components by weight: 70 parts of acrylate monomer, 1 part of crosslinking agent, 0.5 part of initiator, 10 parts of tackifying resin, 15 parts of polyurethane foaming agent, 1 part of cellulose nanocrystals, 3 parts of titanium dioxide nanoparticles, 1 part of chitosan nanofibers, and 3 parts of hydroxyapatite. The tackifying resin is hydrogenated rosin ester.

[0019] In this embodiment, the crosslinking agent is divinylbenzene and the initiator is benzoyl peroxide.

[0020] The present invention provides a preparation process for an acrylic foam tape, comprising the following steps: S1, monomer mixing and preliminary stirring. Maintain the rotation speed in the range of 500 r / min in the stirring kettle. First, put in the acrylate monomer, and add the crosslinking agent, initiator, and tackifying resin under stirring. Control the temperature in the kettle to be maintained in the range of 50 °C to obtain a preliminary mixture. S2, dynamic polymerization. Control the stirring intensity and monomer feeding sequence of the preliminary mixture. Alternately switch the stirring speed at 400 r / min through variable-frequency stirring. Maintain the reaction temperature at 65 °C. When the viscosity reaches the threshold, obtain a dynamic polymer material. S3, nanomaterial dispersion and mixing. Transfer the dynamic polymer material to a shear mixer, put in cellulose nanocrystals, titanium dioxide nanoparticles, chitosan nanofibers, and hydroxyapatite, and control the temperature in the range of 45 °C to obtain a nanodispersion. S4, pulsed light source-induced polymerization. Introduce a photosensitive initiator into the nanodispersion, and perform intermittent irradiation using a pulsed ultraviolet light source. Stir at a stirring speed in the range of 200 r / min during the pulse interval. After irradiating for 30 min, obtain an ultraviolet-excited material. S5, progressive crosslinking. Perform segmented compatibility of the crosslinking agent and the initiator on the ultraviolet-excited material. Inject the remaining amount of the crosslinking agent in multiple times, and add the initiator step by step. Control the temperature in the range of 55 °C, and maintain the fluidity of the material at a stirring speed in the range of 200 r / min for 60 minutes to obtain a gradient crosslinked material. S6. Uniform dispersion of nanoparticles is induced by a pulsed light source. Pulsed ultraviolet excitation is applied inside the gradient cross-linked material. The light source frequency is set in the range of 40 Hz. Medium-speed stirring is used during the pulse interval, and the rotation speed is controlled in the range of 250 r / min. After 15 minutes of irradiation, a uniformly dispersed nanoparticle material is obtained. S7. Foam formation and curing. A polyurethane foaming agent is added to the uniformly dispersed nanoparticle material, and the mixing temperature is controlled in the range of 65 °C. The stirring speed is adjusted to the range of 300 r / min, and the reaction time is maintained for 40 minutes. The foaming process is judged by monitoring the pore uniformity. After the foaming stage is completed, the temperature is reduced to room temperature and left standing for 24 hours to obtain an acrylic foam tape.

[0021] In this embodiment, in step S1, the stirring time of the stirring kettle is 20 minutes.

[0022] In this embodiment, in step S3, the shear mixer stirs at a rotation speed in the range of 4000 r / min for 30 minutes to obtain a nano-dispersion.

[0023] In this embodiment, in the intermittent irradiation of step S4, the light source frequency is controlled in the range of 15 Hz.

[0024] Example 2. The present invention provides an acrylic foam tape. Different from Example 1, the acrylic foam tape comprises the following components in parts by weight: 70 parts of acrylate monomer, 0.6 part of cross-linking agent, 0.6 part of initiator, 25 parts of tackifying resin, 10 parts of polyurethane foaming agent, 4 parts of cellulose nanocrystals, 3 parts of titanium dioxide nanoparticles, 3 parts of chitosan nanofibers, and 3 parts of hydroxyapatite. The tackifying resin is hydrogenated rosin ester.

[0025] Experimental method: 180° peel strength test method: This test adopts the peel strength test method with reference to the standards of GB / T 2792 or ASTM D3330. The prepared acrylic foam tape is cut into specimens with a width of 25 mm and pasted on the surface of a steel plate that has been cleaned and dried. It is rolled twice to ensure firm adhesion. After being placed at room temperature for 24 hours, the specimen is fixed on the fixture of a tensile testing machine, and the specimen is peeled at a 180° direction. The peeling speed is set at 300 mm / min, and the force value when the specimen undergoes continuous peeling is recorded and converted to N / 25 mm. The test needs to be repeated 5 times under constant temperature and humidity conditions, and the average value is taken as the final result of the 180° peel strength.

[0026] Shearing Strength Test Method: The shearing strength test is carried out according to the method of GB / T 7124 or ASTM D1002. First, cut the acrylic foam tape into specimens of 25mm×25mm and adhere them to the surface-treated metal substrate, with the overlap length controlled at 12.5mm. After standing at room temperature for 24 hours, place the overlap area in the upper and lower clamps of the tensile testing machine and conduct tensile shear at a speed of 1.0mm / min until the specimen fails. Record the maximum destructive force and convert it to MPa for representation. Before the test, ensure that the surface of the substrate is flat and clean, and the temperature and humidity of the test environment are stable to ensure the comparability of the test data.

[0027] Impact Toughness Test Method: The impact toughness test is carried out with reference to ASTM D950 (Impact Peel or Impact Test) or similar national standards. Bond the prepared tape to two metal test pieces of the same size and with the same surface treatment method, ensuring that the bonding area and pressure are consistent. After the sample is placed in the standard laboratory conditions for 24 hours, use a pendulum or drop hammer of a specified mass to conduct an impact test on the test piece. During the test, record the energy absorbed when the bonding interface is damaged under the action of the impact energy, and characterize the impact toughness in the form of J / m². The test needs to be repeated multiple times and the average value is taken.

[0028] Dynamic Adhesion Retention Test Method: Use standards such as GB / T 4851 or PSTC-7 to evaluate the dynamic adhesion retention. First, cut the tape into 25mm wide, paste it on the surface of the clean steel plate, and leave about 50mm non-bonding area at the upper end for fixing the clamp. Use a 2kg or corresponding weight rolling roller to compact back and forth and stand at room temperature for 24 hours. Then hang the sample on the adhesion retention test rack, suspend a weight of a defined weight (such as 1kg) at the lower end, and vertically stand and observe it in an environment with relatively constant temperature and humidity, and record the time (in hours) when the specimen undergoes displacement or peeling under this load. The longer the adhesion retention, the better the stability of the tape under dynamic stress.

[0029] Weather Resistance Test Method: The weather resistance test can be carried out in combination with the GB / T 16422 series or ASTM G154 method to simulate outdoor ultraviolet light, humidity, high temperature and other environments. Paste the cut foam tape on the specially treated sample plate, put it into the weather resistance test chamber, and set the ultraviolet light source, spraying and condensation cycle. The cycle is usually set to several hours or days. For example, conduct a cycle of 8 hours of ultraviolet irradiation, 4 hours of condensation or spraying, and continue for several days according to the test standard. After the cycle ends, observe and record the surface state of the tape, the adhesion strength retention rate or the change in optical appearance, and characterize its weather resistance performance in terms of days or retention rate.

[0030] Antibacterial Rate Test Method: Select Escherichia coli as the indicator bacteria for the test, smear it on the surface of the foam tape for one hour and then measure the reduction rate of the bacteria.

[0031] The finished materials prepared in Examples 1-2 were tested. Comparative Example 1 was a foam strong adhesive EVA foam double-sided tape of the Huanguan brand with the product number 0.0.8. The experimental results are as follows: Table 1 Performance test data Performance Index Comparative Example 1 Example 1 Example 2 180° Peel Strength (N / 25mm) 15.2 18.5 19.1 Shear Strength (MPa) 0.68 0.85 0.92 Impact Toughness (J / m²) 32 48 51 Dynamic Adhesion Retention (h) 80 120 130 Weather Resistance (days) 60 90 95 Antibacterial Rate (%) 80.2 98.3 99.1 As can be seen from Table 1, Examples 1-2 have better peel strength, higher shear strength and impact toughness compared to Comparative Example 1, and also show more excellent stability and durability in terms of dynamic adhesion retention and weather resistance. These excellent properties enable the present invention to provide a more reliable and lasting bonding effect during application, enhancing the resistance to external environments and mechanical impacts. Due to the more uniform distribution of the nano-enhanced components inside the material, the synergistic advantages of the bonding function and the foaming structure are further ensured.

Claims

1. An acrylic foam tape, characterized in that: The acrylic foam tape comprises the following components in parts by weight: 50-70 parts of acrylate monomer, 0.1-1 parts of cross-linking agent, 0.1-0.5 parts of initiator, 10-30 parts of tackifying resin, 5-15 parts of polyurethane foaming agent, 1-5 parts of cellulose nanocrystals, 0.5-3 parts of titanium dioxide nanoparticles, 1-3 parts of chitosan nanofibers, and 1-3 parts of hydroxyapatite.

2. The acrylic foam tape according to claim 1, characterized in that: The crosslinking agent is divinylbenzene, trimethylolpropane triacrylate or ethylene glycol diacrylate, and the initiator is dibenzoyl peroxide, di-tert-butyl peroxide or azobisisobutyronitrile.

3. A process for preparing the acrylic foam tape according to claim 1 or 2, characterized in that: The following steps are involved: S1, monomer mixing and preliminary stirring, maintaining a rotation speed in the range of 230-500r / min in the stirring kettle, firstly adding the acrylate monomer, and adding the crosslinking agent, initiator and tackifying resin under stirring, controlling the temperature in the kettle to maintain in the range of 50-60°C, to obtain a preliminary mixture; S2, dynamic polymerization, controlling the stirring intensity and monomer feeding order of the preliminary mixture, switching the stirring speed alternately within the range of 200-400 r / min by variable frequency stirring, maintaining the reaction temperature within the range of 55-65° C., and obtaining a dynamic polymerization material when the viscosity reaches a threshold value; S3, nanomaterial dispersion and mixing, transferring the dynamic polymer material to a shear mixer, adding cellulose nanocrystals, titanium dioxide nanoparticles, chitosan nanofibers and hydroxyapatite, controlling the temperature in the range of 35-45° C., and obtaining a nanodispersion; S4, pulse light source induced polymerization, introducing a photosensitive initiator into the nano-dispersion, and intermittently irradiating with a pulsed ultraviolet light source, stirring at a stirring speed of 100-200 r / min in the pulse interval, and obtaining an ultraviolet excited material after irradiation for 10-30 minutes.

4. The process for preparing the acrylic foam tape according to claim 3, characterized in that: Also includes: S5, gradual crosslinking, performing segmented crosslinking of the UV-excited material with the initiator, injecting the reserved crosslinking agent in multiple times, and adding the initiator in steps, controlling the temperature in the range of 45-55°C, and maintaining the fluidity of the material at a stirring speed in the range of 100-200 r / min for 30-60 minutes to obtain a gradient crosslinked material; S6, a pulse light source is used to induce uniform dispersion of nanoparticles, pulsed ultraviolet excitation is applied inside the gradient cross-linked material, the frequency of the light source is set in the range of 20-40 Hz, medium-speed stirring is used during the pulse interval, the rotation speed is controlled in the range of 150-250 r / min, and after continuous irradiation for 10-15 minutes, a nano-uniformly dispersed material is obtained; S7, foam formation and maturation, adding a polyurethane foaming agent to the nano-uniformly dispersed material, and controlling the mixing temperature in the range of 65-75°C, adjusting the stirring speed to the range of 150-300r / min, maintaining the reaction time for 30-40 minutes, judging the foaming progress by monitoring the uniformity of the pores, and after the foaming stage is completed, cooling to room temperature and standing for 12-24 hours to obtain an acrylic foam tape.

5. The process for preparing the acrylic foam tape according to claim 3, characterized in that: In step S1, the stirring time of the stirring tank is 10-20 minutes.

6. The process for preparing the acrylic foam tape according to claim 3, characterized in that: In step S3, the shear mixer is stirred at a rotation speed of 3000-4000 r / min for 15-30 minutes to obtain a nano-dispersion.

7. The process for preparing the acrylic foam tape according to claim 3, characterized in that: In the intermittent irradiation of step S4, the frequency of the light source is controlled in the range of 5-15 Hz.